Predictors of durable electrical isolation in the setting of second‐generation cryoballoon ablation: A comparison between left superior, left inferior, right superior, and right inferior pulmonary veins. (4th December 2019) - Scala, Oriana; Borio, Gianluca; Paparella, Gaetano; Varnavas, Varnavas; Ströker, Erwin; Guimaraes Osorio, Thiago; Terasawa, Muryo; Sieira, Juan; Maj, Riccardo; Rizzo, Alessandro; Al‐Hosari, Maysam M.; Galli, Alessio; et al.
Abstract: Aim: The aim of this study is to assess specific per‐vein procedural predictors of pulmonary vein (PV) late reconnection in cryoballoon ablation (CbA) Methods and Results: We enrolled 148 consecutive patients undergoing a redo procedure after a previous index CbA in our center. A reconnection in at least one PV was found in 80 patients (54.1%) and the most frequently reconnected PV was the right inferior pulmonary vein (RIPV). Overall, pulmonary vein reconnection (PVr) was associated with longer time to −40°C (Tt−40°C) (54.4 ± 21.7 vs 67.6 ± 27.6 seconds; P  < .001), warmer nadir temperature (NT) (−49.7°C ± 5.4°C vs −46.5°C ± 5.8°C; P  < .001) and temperature at 60 seconds (−41.8°C ± 4.5°C vs −39.8°C ± 4.2°C; P  < .001). The performance of these predictors differed between the veins. In particular, a comparable behavior was observed for left superior pulmonary vein (LSPV) and right superior pulmonary vein (RSPV), where NT ≤ −48°C showed a sensibility and a specificity, respectively, of 62% and 65% and 71% and 72% in predicting durable PV isolation. For RIPV, NT ≤ −48°C showed a sensitivity of 74% but low specificity (53%). Tt −40°C less than 60 seconds showed good negative predictive values, respectively, 83.9% for LSPV, 94.9% for left inferior pulmonary vein (LIPV), 90.2% for RSPV, and 82.7% for RIPV. Previous predictors cannot be used for LIPV. Conclusions: Freezing behavior and reconnection rates differ significantly among the four PVs. Freezing temperature parameters strongly predict late PVr in superior PVs and are slightly different in RIPV but can be applied as well. LIPV freezing behavior is the most different. Its reconnection is uncommon even in the subset of worse freezing temperatures and specific CB predictors cannot be identified.